Strategic Choice Handicaps when Females Pay the Cost of the Handicap - Georg Nöldeke; Larry Samuelson (University of Bonn, Bonn Graduate School of Economics (BGSE), 2001)
We examine a strategic-choice handicap model in which males send costly signals to advertise their quality to females. Females are concerned with the net viability of the male with whom they mate, where net viability is a function of the male's quality and signal. We identify circumstances in which a signaling equilibrium would require high-quality males to send signals so much larger than those of males in lower quality (to deter mimicry by the latter) as to yield lower net viabilities for the former. This causes females to shun males who send large signals, ensuring that there is no signaling equilibrium.
Keywords: C72; D82; 330; sexual selection; handicap principle; signaling equilibrium; net viability